2018
DOI: 10.1111/mmi.13927
|View full text |Cite
|
Sign up to set email alerts
|

Independent and cooperative regulation of staphylopine biosynthesis and trafficking by Fur and Zur

Abstract: Staphylococcus aureus expresses the Cnt system implicated in the active transport of trace metals by synthesizing (CntKLM) and exporting (CntE) staphylopine, a metallophore chelating metals and then taken up by an ABC-transporter (CntABCDF). This machinery is encoded in the cntKLMABCDFE operon, preceded by a non-coding region (PcntK) and containing an internal promoter region (PcntA). PcntK comprises a Fur box followed by a Zur box, a sRNA transcription start and a repeated region, while PcntA comprises a Fur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 61 publications
(103 reference statements)
2
53
0
2
Order By: Relevance
“…The fitness defect of DcntE mutant associated with intracellular StP accumulation occurred in both metal-depleted laboratory media as well as in sites of infection. Our work and that of others showed that Fe or Zn availability repressed the expression of cntKLM [17][18][19]. Besides StP, S. aureus produces other siderophores including SA and SB [11].…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The fitness defect of DcntE mutant associated with intracellular StP accumulation occurred in both metal-depleted laboratory media as well as in sites of infection. Our work and that of others showed that Fe or Zn availability repressed the expression of cntKLM [17][18][19]. Besides StP, S. aureus produces other siderophores including SA and SB [11].…”
Section: Discussionsupporting
confidence: 65%
“…Disruption of the StP biosynthesis gene cntL eliminated intracellular StP accumulation and alleviated the growth defect of DcntE mutant. Under metal-rich conditions, activated Fur or Zur binds to the fur/zur box at the promoter regions of cnt operon and mediates repression of transcription of StP synthesis genes cntKLM and thus prevents the overproduction of StP [19]. SA accumulates in the cytoplasm of S. aureus in the absence of SA exporter SfaA, but unlike StP, the accumulation of SA does not cause a fitness defect or other apparent adverse effects in S. aureus [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations